Policy innovation in a weak democracy - Balboa, Jenny D. (Quezon City, Philippines : Ateneo De Manila University Press, 2023)
For many developing economies with colonial history, the prospect of trade liberalization almost always hits a raw nerve, given how unfair trade policy was imposed on them in the past.
Chapter 1. Introduction -- Chapter 2. Neoliberalism -- Chapter 3. Beyond Neoliberalism: ASEAN's Pragmatism and Developmentalism -- Chapter 4. Historical Antecedents of the Trade Reforms: From Colonial Period to the Marcos Era. --Chapter 5. Trade Policy and AFTA in the Redemocratization Years -- Chapter 6. Explaining Trade Liberalization and AFTA Accession in the Aquino Years -- Chapter 7. Explaining the Sustenance of Trade Reforms and AFTA in the Ramos Years -- Chapter 8. Conclusion.
Includes index.
Keywords: FREE TRADE -- PHILIPPINES -- 1986-1998